Stress Regimes and Stress Fields Analysis Using Fault-Slip Data; Eastern Iran - Ezati, Maryam; Gholami, Ebrahim; Mousavi, Seyed M.; Ezati, Mohsen (Global Journal of Earth Science and Engineering, 2023)
In this paper direction of stress tensors and stress ellipsoids shape in Neogene, Paleogene, and older units were investigated. Moreover, relationship between shape of stress ellipsoid and exhumation of igneous units were determined using analysis of stress tensors. Analysis of relationships between stress regime and uplifting indicate that in the areas we observed the uplifting of the igneous units the shape of stress ellipsoid has been displaced locally from prolate to oblate which is due to local change of stress regime. Hence, local variation of stress regime in the eastern part of Shekarab Mountains caused boarder outcrops of igneous units. In the western part of study area shape of stress ellipsoid is prolate and it’s due to existing reverse fault with strike-slip component. Comparison shape of stress ellipsoid in Eocene units indicate that shape of stress ellipsoid in the western, middle and eastern Shekarab Mountains is prolate, and as local there is oblate stress ellipsoid shape in eastern part. Results of this research indicate that direction of major stress axis had clockwise rotation from Cretaceous times to the present.